NADPH oxidase 4 promotes endothelial angiogenesis through endothelial nitric oxide synthase activation - Craige, Siobhan M; Chen, Kai; Pei, Yongmei; Li, Chunying; Huang, Xiaoyun; Chen, Christine; Shibata, Rei; Sato, Kaori; Walsh, Kenneth; Keaney, Jr, John F (Circulation (New York, N.Y.), 2011)
BACKGROUND- Reactive oxygen species serve signaling functions in the vasculature, and hypoxia has been associated with increased reactive oxygen species production. NADPH oxidase 4 (Nox4) is a reactive oxygen species-producing enzyme that is highly expressed in the endothelium, yet its specific role is unknown. We sought to determine the role of Nox4 in the endothelial response to hypoxia. Hypoxia induced Nox4 expression both in vitro and in vivo and overexpression of Nox4 was sufficient to promote endothelial proliferation, migration, and tube formation. To determine the in vivo relevance of our observations, we generated transgenic mice with endothelial-specific Nox4 overexpression using the vascular endothelial cadherin promoter (VECad-Nox4 mice). In vivo, the VECad-Nox4 mice had accelerated recovery from hindlimb ischemia and enhanced aortic capillary sprouting. Because endothelial nitric oxide synthase (eNOS) is involved in endothelial angiogenic responses and eNOS is activated by reactive oxygen species, we probed the effect of Nox4 on eNOS. In cultured endothelial cells overexpressing Nox4, we observed a significant increase in eNOS protein expression and activity. To causally address the link between eNOS and Nox4, we crossed our transgenic Nox4 mice with eNOS(-/-) mice. Aortas from these mice did not demonstrate enhanced aortic sprouting, and VECad-Nox4 mice on the eNOS(-/-) background did not demonstrate enhanced recovery from hindlimb ischemia. Collectively, we demonstrate that augmented endothelial Nox4 expression promotes angiogenesis and recovery from hypoxia in an eNOS-dependent manner.